MEASURING THE ATTRACTIVENESS OF MEMBERSHIP CARDS IN MAINTAINING CUSTOMER LOYALTY (CASE STUDY AT INDOMARET FRESH MAUMBI WATUTUMOU STORE) - Fransisca H.Manueke; Rio Hasan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This study aims to determine the effect of membership card appeal on customer loyalty at Indomaret Fresh Watutumou. The background of this study is based on the importance of membership-based marketing strategies in retaining customers and increasing repeat visits. This study uses a quantitative approach with a survey method by distributing questionnaires to 30 respondents who are Indomaret Fresh Watutumou customers. Data analysis was carried out using simple linear regression with the help of SPSS version 25. The results showed that the appeal of membership cards had a significant effect on customer loyalty. This is indicated by the coefficient of determination (R²) value of 0.672, which means that 67.2% of the variation in customer loyalty can be explained by the appeal of membership cards. The correlation coefficient (R) value of 0.820 indicates a very strong relationship between the two variables. In addition, the results of the t-test show a significance value of 0.000 <0.05, which indicates that the effect is significant. Thus, it can be concluded that the higher the appeal of membership cards felt by customers, the higher their level of loyalty. This study provides important implications for Indomaret management in designing more attractive membership programs to maintain and increase customer loyalty